Bandgap tuning and optimization of green-emitting Zn2SnO4-Mg2SnO4:Mn2+ using combinatorial pulsed laser deposition. Issue 13 (September 2020) - Dazai, Takuro; Yasui, Shintaro; Taniyama, Tomoyasu; Itoh, Mitsuru
Abstract: We investigated a compositional spread Mn 2+ -doped Zn2 SnO4 -Mg2 SnO4 (Mn-ZMTO) film prepared by combinatorial pulsed laser deposition. The composition of the prepared film gradually changed from Zn2 SnO4 (ZTO) to Mg2 SnO4 (MTO). Moreover, the lattice constant decreased with an increase in MTO composition. Under ultraviolet irradiation, the film exhibited bright green luminescence attributable to the transition from 4 T1 to 6 A1 of Mn 2+ . This is the report of the observation of green luminescence from Mn-ZMTO on the ZTO-rich side. In addition, the most intense luminescence was located at the center of the sample. The emission intensity and the most intense position were changed by irradiation at various excitation wavelengths. This was clarified by the positional dependence of PLE spectra. The bandgap of the prepared film, which corresponded to the PLE peak wavelength, was larger than that of the bulk material and increased with an increase in Mg concentration. Since emission cannot usually be observed from Mn-doped ZTO, we suggest that the luminescence from the prepared film was caused by an increase in the bandgap attributable to the 1-dimentional thin film size effect along thickness direction. Thus, using the thin film technique we revealed that bandgap tuning is important in phosphor material.